"... from teat-jerk to quidnunc": A.R.D. Fairburn and the Formation of an Ideology of Architectural Nationalism in New Zealand - Wood, Peter (Architectural History Aotearoa, 2006)
In 1934 ARD Fairburn published the essay "Some Aspects of N.Z. Art and Letters" in the journal Art in New Zealand. In it he criticized Alan Mulgan's book Home: A Colonial's Adventure, which had been first published in 1927, and was reprinted in 1934. It was, in Fairburn's view, an account unacceptably steeped in romantic melancholy for a distant motherland that was no longer as germane as it had once been. Instead he proposed looking to the American Transcendentalists Twain and Thoreau for direction. Also published in 1934 was a small book from the New Zealand Institute of Architects called Building in New Zealand. In it the NZIA made a case for the professional and social responsibilities of the architect in New Zealand and it is best described as conservative. However it is pertinent that this book was edited by Alan Mulgan. Here the role of the architect in cast in practical terms that bear direct comparison to the code of practice issue for the Royal Institute of British Architects. Mulgan's contribution to discussion on New Zealand architecture is limited to this publication, and it is likely his editorship of Building in New Zealand was motivated more by depression economics than architectural interest. However this book is still an important summary of the profession at that time, and it links architecture to Mulgan's romantic writings though the reiteration of a colonial fountainhead. By contrast Fairburn would go on to champion a national voice for New Zealand's writers, artists, and architects. Moreover he established a close relationship with Vernon Brown, and was to associate with Bill Wilson and the Architectural Group. Indeed, the limited writings available from these architectural associates often echo Fairburn's 1934 call for an antipodean "honesty" in "our" buildings. It is in the immediate post war period that the emergence of a national architectural expression in New Zealand is most celebrated, being lead in Auckland by Brown, Wilson, and the Architectural Group. However an examination of the writings by Fairburn and Mulgan shows that the elements of the debate were already in place well before then. I conclude that the antecedent for the emergence of debate on a national architectural character appears, however unintentionally, in the 1934 writings of Fairburn and Mulgan. Critical to this is discussion on we mean by "honest" architectural work.